ECO-INNOVATION AND SUSTAINABLE ENTREPRENEURSHIP IN THE ERA OF GLOBALIZATION - Berik Kazakbayev (Modern American Journals, 2025)
This article analyzes the role of eco-innovations as a key factor in the development of sustainable entrepreneurship in the context of globalization. The paper identifies the main vectors for the implementation of environmental technologies and practices, and analyzes the barriers and challenges that enterprises face. Examples of successful integration of eco-innovations into business models are given, and recommendations for their adaptation in the context of developing economies are formulated.
Keywords: Eco-innovation, sustainable entrepreneurship, globalization, green economy, corporate sustainability.